Ethnic, Culture, Religion, Lingu ETHNIC CONFLICT OF BODO PEOPLE OF ASSAM STATE IN INDIA: Indian Government and Politics - vadranam, Dr Sursh (International research journal of management, IT and social sciences, 2022)
India has till now 29 states and 7 union territories where the North east India has 8 states. The seven states which include Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Tripura we called it as seven sisters and Sikkim is the brother of them. These states cover a combined range of cover 255,088 sq.km (7.7 percent) of the country’s region. ‘World meter’ said that current population of India is 1,377,233,523 as of Saturday, April18, 2020, where the population of North east India is 38.49 million.[1] The term ‘North-east’ was indicated by the colonial ruler the Britishers as a wilderness locale. The north east India was associated to the most heartland India through the 21 km wide Siliguri passage, which is known as the ‘chicken neck’ made by the Redcliff line.[2] North eastern states are surrounded by many countries. It shares many international borders like China, Bangladesh, Nepal, Bhutan, and Myanmar. North eastern region is consisting of extraordinary ethnic, culture, religion and linguistic diversity [1] (worldometers) [2] Jagadish K. Patnaik. "Mizo Identity and Indianisation: A Case of Conflict Transformation in Mizoram" , Indian Journal of Public Administration, 2017